Structural Plasticity on the SpiNNaker Many-Core Neuromorphic System - Bogdan, Petruț A.; Rowley, Andrew G. D.; Rhodes, Oliver; Furber, Steve B. (Frontiers in Neuroscience, 2018)
The structural organisation of cortical areas is not random, with topographic maps commonplace in sensory processing centres. This topographical organisation allows optimal wiring between neurons, multimodal sensory integration, and performs input dimensionality reduction. In this work, a model of topographic map formation is implemented on the SpiNNaker neuromorphic platform, running in realtime using point neurons, and making use of both synaptic rewiring and spike-timing dependent plasticity (STDP). In agreement with \cite{Bamford2010}, we demonstrate that synaptic rewiring refines an initially rough topographic map over and beyond the ability of STDP, and that input selectivity learnt through STDP is embedded into the network connectivity through rewiring. Moreover, we show the presented model can be used to generate topographic maps between layers of neurons with minimal initial connectivity, and stabilize mappings which would otherwise be unstable through the inclusion of lateral inhibition.